Analyzing in the Present. (April 2015) - Revsbæk, Line; Tanggaard, Lene
The article presents a notion of "analyzing in the present" as a source of inspiration in analyzing qualitative research materials. The term emerged from extensive listening to interview recordings during everyday commuting to university campus. Paying attention to the way different parts of various interviews conveyed diverse significance to the listening researcher at different times became a method of continuously opening up the empirical material in a reflexive, breakdown-oriented process of analysis. We argue that situating analysis in the present of analyzing emphasizes and acknowledges the interdependency between researcher and researched. On this basis, we advocate an explicit "open-state-of mind" listening as a key aspect of analyzing qualitative material, often described only as a matter of reading transcribed empirical materials, reading theory, and writing. The article contributes to an ongoing methodological conversation problematizing the notion of "data" and the use of "data-reliant" methods of analysis.